Evaluation of the Occupational Health and Safety Work Environment at PT. Japfa Comfeed Indonesia Tbk. Gedangan – Sidoarjo Unit - Riza Irianingtyas; Endang Dwiyanti; Alen Prahadinata (Universitas Airlangga, 2022)
Introduction: An Occupational Health and Safety (OHS) work environment is defined as all activities undertaken to ensure and protect the health and safety of workers through the controlling of the working environment and the implementation of sanitation and hygiene principles in the workplace with the aim of creating a safe and healthy working environment to minimize the risk of accidents and illness. The purpose of this study was to evaluate the suitability of occupational health and safety (OHS) in the working environment of PT Japfa Comfeed Indonesia Tbk. Gedangan – Sidoarjo Unit based on the regulation of Minister of Manpower No. 5/2018. Methods: This research was descriptive and qualitative. The data used was primary and secondary. The primary data are taken from the Company Health Safety Environment (HSE) Department and the secondary data was from the company measurement results and documentation. Result: The results show that the measurement and control of the risk factors was quite good but there were still inconsistencies, namely room temperature which still exceeded the provisions, and the measurement and control of ergonomic and psychological factors which had not been implemented. The availability of hygiene facilities and the infrastructure in the company was classified as good and supports the work activities but it still needs improvement including the presence of a sewer that is not closed, and the air quality in the rooms and the trash still not meeting the standards. Conclusion: The implementation of Occupational Health and Safety (OHS) in the working environment of PT. Japfa Comfeed Indonesia Tbk. The Gedangan-Sidoarjo Unit based on the Minister of Manpower Regulation No. 5/2018 is quite good but there are several aspects where improvement is necessary.